Assessment of Thrombotic and Bleeding Tendency in Two Mouse Models of Chronic Kidney Disease: Adenine-Diet and 5/6th Nephrectomy - Makhloufi, Camélia; Crescence, Lydie; Darbousset, Roxane; McKay, Nathalie; Massy, Ziad A.; Dubois, Christophe; Panicot-Dubois, Laurence; Burtey, Stéphane; Poitevin, Stéphane (TH Open, 2020)
The coexistence of bleeding and thrombosis in patients with chronic kidney disease (CKD) is frequent and poorly understood. Mouse models are essential to understand complications of CKD and to develop new therapeutic approaches improving the health of patients. We evaluated the hemostasis in two models of renal insufficiency: adenine-diet and 5/6th nephrectomy (5/6Nx). Compared with 5/6Nx mice, mice fed with 0.25% adenine had more severe renal insufficiency and so higher levels of prothrombotic uremic toxins like indoxyl sulfate. More severe renal inflammation and fibrosis were observed in the adenine group, as demonstrated by histological and reverse transcription quantitative polymerase chain reaction experiments. Liver fibrinogen γ chain expression and level of plasma fibrinogen were increased only in adenine mice. In both CKD mouse models, tissue factor (TF) expression was increased in kidney and aorta extracts. Immunochemistry analysis of kidney sections showed that TF is localized in the vascular walls. Thrombin–antithrombin complexes were significantly increased in plasma from both adenine and 5/6Nx mice. Tail bleeding time increased significantly only in adenine mice, whereas platelet count was not significant altered. Finally, results obtained by intravital microscopy after laser-induced endothelial injury showed impaired platelet function in adenine mice and an increase in fibrin generation in 5/6Nx mice. To summarize, adenine diet causes a more severe renal insufficiency compared with 5/6Nx. The TF upregulation and the hypercoagulable state were observed in both CKD models. Bleeding tendency was observed only in the adenine model of CKD that recapitulates the whole spectrum of hemostasis abnormalities observed in advanced human CKD.
Keywords: tissue factor; platelets; hemostasis